Finding a suitable DNA barcode for Mesoamerican orchids - Gigot, Guillaume (2015)
Recently, DNA barcoding has emerged as an effec- tive tool for species identification. This has the poten- tial for many useful applications in conservation, such as biodiversity inventories, forensics and trade sur- veillance. It is being developed as an inexpensive and rapid molecular technique using short and standard- ized DNA sequences for species identification.